Postural Control Complexity and Fatigue in Minimally Affected Individuals with Multiple Sclerosis - Santinelli, Felipe B. [UNESP]; Barbieri, Fabio A. [UNESP]; Pinheiro, Carina F.; Amado, Avelino C.; Sebastião, Emerson; van Emmerik, Richard E. A. (Taylor & Francis, 2019)
This study investigated changes in postural control complexity in people with multiple sclerosis (PwMS) before and after a fatigue protocol. Thirteen minimally affected PwMS (1.53 ± 1.03- Expanded Disability Status Scale) and 12 non-MS controls. Postural test included quiet stance on a force platform under two visual conditions (saccades and fixation) before and after a fatigue protocol. Postural complexity was assessed through the multiscale entropy. A three-way ANOVA showed a main effect of fatigue in the medial-lateral direction (p <0.007), with fatigue protocol reducing postural complexity in both groups. No differences were found between groups or visual conditions. Minimally affected PwMS demonstrated similar postural complexity compared with non-MS controls under both visual tasks and showed similar decrements in postural complexity as a result of fatigue.
Keywords: fatigue; Multiple sclerosis; multiscale entropy; postural control